The Role of Faculty Development in Enhancing Teaching Quality in Higher Education in Pakistan - Dr. Shakeel Ahmed; Tahira Naudhani; Dr. Shams Wazir (Social Science Review Archives, 2025)
The present study analyzes how faculty development contributes to teaching quality in higher education institutions in Pakistan. It adopts a mixed-methods research strategy. The investigation covers faculty development programs and teaching effectiveness among 300 faculty members and 50 academic administrators from public and private universities in Pakistan. Researchers administered a structured questionnaire on teaching effectiveness, attendance rate, and perceived impact. They also conducted semi-structured interviews to gather qualitative insights. Statistical data indicated a substantial positive correlation between participation in faculty development and indicators of teaching effectiveness. The explanatory power of comprehensive professional development programs accounts for 67% of the possible variance in teaching quality indicators. The qualitative analysis summarized the importance of pedagogical training, technology integration workshops, and peer collaboration initiatives in improving instructional practices. High levels of institutional support, resource availability, and program relevance were identified as key factors influencing faculty participation. Findings reveal that formal faculty improvement programs enhance teaching levels, student satisfaction, and overall performance at Pakistan’s higher-education institutions. This study can guide policymakers and administrators seeking to improve faculty performance through development initiatives and activities.